The necessity and the general principles of intervention in the deteriorated urban areas - Rezaee , Naimeh (2008)
The deteriorated urban areas are the problems that cannot be ignored in the contemporary cities. These textures confront various problems and not paying attention to these fabrics will result in the lost of live in them. These problems can be mentioned in brief as follows: inconsistency with urban structure, high population density, decreased physical/social/economic and environmental quality, etc. The problems of the deteriorated areas are mostly multi-aspect. Therefore solving these problems needs various programs and measures each of which focuses on a particular aspect. According to experiences, the one-aspect approach to urban fabric is not much useful. Therefore interfering in these textures should be made in all physical, social and economic aspects. What is of the most importance in the preparation of the projects for these areas, is the deep, extended, and multidimensional studies before starting the planning phase. On the other hand, the topic that has been considered as a principle in these projects is the people’s participation.